1998
DOI: 10.1046/j.1365-3083.1998.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Induction in C57BL/6 Mice Reconstituted with Lymphocytes of Nonobese Diabetic <−> C57BL/6 Mouse Embryo Aggregation Chimeras

Abstract: To determine whether the genetic background of the insulin-producing beta cells of the pancreas contributes to autoimmune diabetes susceptibility, we have used a model of the disease based on transferring spleen cells from nonobese diabetic (NOD) <--> C57BL/6 (B6) embryo aggregation (EA) chimeras into B6 and NOD irradiated mice. Insulitis and diabetes could be induced into both B6 and NOD hosts, albeit with low incidence. Cyclophosphamide (CY) treatment, known to accelerate diabetes in prediabetic NOD mice, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…CTLA-4 could negatively regulate T cell proliferation. In 1998, Colucci et al found deficiency in CTLA-4 expression in non-obese diabetic (NOD) mice, suggesting that CTLA-4 might be involved in the pathogenesis of T1DM [28]. In 2004, Vijayakrishnan et al found that the expression of ligand-independent CTLA-4 (liCTLA-4) lacking B7-binding domain signals was higher in memory/regulatory T cells from diabetes-resistant NOD congenic mice compared with susceptible NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…CTLA-4 could negatively regulate T cell proliferation. In 1998, Colucci et al found deficiency in CTLA-4 expression in non-obese diabetic (NOD) mice, suggesting that CTLA-4 might be involved in the pathogenesis of T1DM [28]. In 2004, Vijayakrishnan et al found that the expression of ligand-independent CTLA-4 (liCTLA-4) lacking B7-binding domain signals was higher in memory/regulatory T cells from diabetes-resistant NOD congenic mice compared with susceptible NOD mice.…”
Section: Discussionmentioning
confidence: 99%